2021
DOI: 10.1002/biot.202100214
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of sugar transporters and glycolysis pathways in Ettlia sp. under heterotrophy using fructose and glucose

Abstract: Fructophilic behavior in microalgae is a rare trait that could benefit biorefineries by enabling substitution of carbon source with fructose, and our previous study identified that Ettlia sp. prefers fructose relative to glucose. In this study, by analyzing the transcription levels of genes related to sugar transport and the glycolysis pathway, the fructose utilization of Ettlia sp. was investigated. In a fructose‐containing medium, the expression levels of fructokinase (EttFRK3) and glucokinase (EttGCK1 and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The third category was enriched in the transport of glucose metabolism, such as “hexose transmembrane transport,” etc. Glucose metabolism is an important process of energy metabolism and substance metabolism in cells, including the synthesis, degradation, and transport of sugar …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third category was enriched in the transport of glucose metabolism, such as “hexose transmembrane transport,” etc. Glucose metabolism is an important process of energy metabolism and substance metabolism in cells, including the synthesis, degradation, and transport of sugar …”
Section: Resultsmentioning
confidence: 99%
“…Glucose metabolism is an important process of energy metabolism and substance metabolism in cells, including the synthesis, degradation, and transport of sugar. 45 To further explore the functions of DEGs in metabolic pathways, KEGG pathway enrichment analysis was conducted on DEGs. Figure 5c lists the top 30 altered enriched pathways changed by KEGG annotation.…”
Section: Influence Of Mixed Absorbent On Algal Gene Expression and Fu...mentioning
confidence: 99%
“…[85] In the H. pluvialis, the pH steady cultivation is accompanied by the increase of biomass accumulation, nitrate consumption and carbon fixation due to increased Ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCo) activity. [86] In addition to CO 2 , carbon can also be supplied as different organic molecules, which typically enhance the microalgae growth, [142,153,154] It was recently reported that a combination of acetate and pyruvate enhanced the Haematococcus lacustris growth twice in mixotrophic in comparison to phototrophic conditions. [153]…”
Section: Co 2 Supplementation and Ph Control Influence Microalgae Growthmentioning
confidence: 99%
“…In addition to CO 2 , carbon can also be supplied as different organic molecules, which typically enhance the microalgae growth, [ 142,153,154 ] It was recently reported that a combination of acetate and pyruvate enhanced the Haematococcus lacustris growth twice in mixotrophic in comparison to phototrophic conditions. [ 153 ]…”
Section: Co2 Supplementation or Genetic Modifications Of Co2 Fixation...mentioning
confidence: 99%